Reconciling Homeostatic and Use-Dependent Plasticity in the Context of Somatosensory Deprivation - John J. Orczyk; Preston E. Garraghty (Neural Plasticity)
The concept of homeostatic plasticity postulates that neurons maintain relatively stable rates of firing despite changing inputs. Homeostatic and use-dependent plasticity mechanisms operate concurrently, although they have different requirements for induction. Depriving central somatosensory neurons of their primary activating inputs reduces activity and results in compensatory changes that favor excitation. Both a reduction of GABAergic inhibition and increase in glutamatergic excitatory transmission are observed in input-deprived cortex. Topographic reorganization of the adult somatosensory cortex is likely driven by both homeostatic and use-dependent mechanisms. Plasticity is induced by changes in the strengths of synaptic inputs, as well as changes in temporal correlation of neuronal activity. However, there is less certainty regarding the in vivo contribution of homeostatic mechanisms as in vitro experiments rely on manipulations that create states that do not normally occur in the living nervous system. Homeostatic plasticity seems to occur, but more in vivo research is needed to determine mechanisms. In vitro research is also needed but should better conform to conditions that might occur naturally in vivo.